Parâmetros fisiológicos de cultivares de cevada sob déficits hídricos - dos Santos, Alexandre Barreto Almeida [UNESP]; Klar, Antonio Evaldo [UNESP]; Jadoski Jr., Cleber [UNESP] (My University, 2008)
The objective of this study was to evaluate some physiological parameters in six barley cultivars (Borema, Lagoa, BRS-180, BRS-195, EMB-128 e BRS-225), under water stress in different crop phenological phases. The treatments were as follows: TI - pots constantly irrigated until harvest: T2: - water stress starting from 45 days after sowing (DAS) and T3 - water stress starting from 65 DAS. Leaf resistance to water vapor diffusion (Rs), relative water content (RWC), and leaf water potential (Ψ1) were used to evaluate drought tolerance. Pots were arranged in a randomized block design with four blocks, six barley cultivars, and three treatments, in a total of seventy two pots. The experiment was conducted from August to November 2005 in a polyethylene greenhouse located at the experimental area of Rural Engineering Department - FCA, UNESP - Botucatu - SP. The results showed that all barley cultivars presented some adaptation to water stress, but EMB-128 was the most likely and BRS-180 the least likely to be drought tolerant. The results revealed that only one drought cycle may increase tolerance to drought.
Physiological parameters in Barley cultivars under water stress
Keywords: And leaf water potential; Leaf resistance to water vapor diffusion; Relative water content; barley; cultivar; drought resistance; phenology; water content; water stress; Bovine respiratory syncytial virus; Hordeum